Association of colchicine use for acute gout with clinical outcomes in acute decompensated heart failure. Issue 7 (28th April 2022) - Roth, Mary E.; Chinn, Melissa E.; Dunn, Steven P.; Bilchick, Kenneth C.; Mazimba, Sula
Abstract: Background: Gout is a common comorbidity in heart failure (HF) patients and is frequently associated with acute exacerbations during treatment for decompensated HF. Although colchicine is often used to manage acute gout in HF patients, its impact on clinical outcomes when used during acute decompensated HF is unknown. Methods: This was a single center, retrospective study of hospitalized patients treated for an acute HF exacerbation with and without acute gout flare between March 2011 and December 2020. We assessed clinical outcomes in patients treated with colchicine for a gout flare compared to those who did not experience a gout flare or receive colchicine. The primary outcome was in‐hospital all‐cause mortality. Results: Among 1047 patient encounters for acute HF during the study period, there were 237 encounters (22.7%) where the patient also received colchicine for acute gout during admission. In‐hospital all‐cause mortality was significantly reduced in the colchicine group compared with the control group (2.1% vs. 6.5%, p  = .009). The colchicine group had increased length of stay (9.93 vs. 7.96 days, p  < .001) but no significant difference in 30‐day readmissions (21.5% vs. 19.5%, p  = .495). In a Cox proportional hazards model adjusted for age, inpatient colchicine use was associated with improved survival to discharge (hazards ratio [HR] 0.163, 95% confidence interval [CI] 0.051−0.525, p  = .002) and a reduced rate of in‐hospital CV mortality (HR 0.184, 95% CI 0.044−0.770, p  = .021). Conclusion: Among patients with a HF exacerbation, treatment with colchicine for a gout flare was associated with significantly lower in‐hospital mortality compared with those not treated for acute gout.